Variation of photovoltaic system performance due to climatic and geographical conditions in Turkey - Bektas Ekici, Betul (Tubitak Scientific & Technological Research Council Turkey, 2016)
This study focuses on the effect of climatic and geographical factors on the performance of photovoltaic systems. For this purpose, 4 different cities (Antalya, Istanbul, Elazig, and Erzurum) from different climatic zones according to TS 825 Thermal Insulation Requirements in Buildings were selected. The monthly average global and diffuse solar radiation of the cities was calculated numerically with the long-term sunshine duration data (between 1990 and 2012) taken from the Turkish State Meteorological Service. The yearly electric energy generated by the grid-connected photovoltaic systems assumed to be located on the flat roofs of building samples were calculated for each of the cities. PVsyst 6.2.6. software was employed for the calculation of yearly energy yield. Consequently, the maximum photovoltaic output was achieved in Elazig and the minimum in Istanbul. The optimum tilt angles for Antalya, Istanbul, Elazig, and Erzurum were obtained as 32 degrees, 36 degrees, 32 degrees, and 35 degrees, respectively.
Keywords: Photovoltaics; PVsyst; flat roofs; optimum tilt angle